2008
DOI: 10.1007/s10995-008-0399-0
|View full text |Cite
|
Sign up to set email alerts
|

Body Size and Intelligence in 6-year-olds: Are Offspring of Teenage Mothers at Risk?

Abstract: Objectives-Children born to teenage mothers are at risk for more physical and cognitive problems than those born to adult mothers. Our objective was to examine differences in size and intelligence between two cohorts of offspring born to adolescent (n = 357) and adult mothers (n = 668) who attended the same prenatal clinic.Methods-Two prospective study cohorts were assessed children from gestation through age 6 years. The adult cohort was studied in the mid-1980's and the teen cohort was evaluated in the mid-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 49 publications
(42 reference statements)
0
23
1
1
Order By: Relevance
“…4,5 Long term follow up studies have shown that the children born to teenage mothers are at higher risk and are usually plagued by intellectual, language, and socio-emotional delays. 6 The female child of an adolescent has higher risk of becoming pregnant herself as a teenager. 7 Also due early initiation of sexual activity and multiple pregnancies these girls become high risk for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Long term follow up studies have shown that the children born to teenage mothers are at higher risk and are usually plagued by intellectual, language, and socio-emotional delays. 6 The female child of an adolescent has higher risk of becoming pregnant herself as a teenager. 7 Also due early initiation of sexual activity and multiple pregnancies these girls become high risk for cervical cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Long term follow up studies have shown that the children born to teenage mothers are at higher risk and are usually plagued by intellectual, language, and socio-emotional delays. [7] Some studies, however have shown that adverse outcomes of teenage pregnancies are more the result of socioeconomic factors rather than the biological age itself.These factors may cause a delay in health care seeking by the mother [8]. This other risk factor, like non-utilization or non accessibility to antenatal care may be more of a contributing factor rather that the young age of the mother [9,10,11] .…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, only 1 study has done so while looking at the associated early-life risk factors. Li and colleagues 11 used 6 assessment points (age 2, 4, 6, 8, 10, and 12 years) and identified 3 developmental trajectories of overweight status among a representative US sample (N=1739): early onset (age 2 years, 10.9%), late onset (age 6 years, 5.2%), and never overweight (83.9%). This study provided useful information on the ages at which 2 pathologic BMI trajectories emerged.…”
mentioning
confidence: 99%